Comparison in Biographie de la faim by Amélie Nothomb - Nascimento, Takiko do (Lettres Françaises, 2009)
This article aims at analyzing the system of comparison and its application in the chapter concerned with “hyperthirst” (sursoif) in the book Biographie de la faim, by Amélie Nothomb. The objective is to show how Nothomb utilizes various procedures of comparison to evoke her childhood memories – a phase of exaltation, in which sensations and feelings are exaggerated. The analysis unravels the utilization of all sorts of comparison procedures, from vocabulary to metaphors, as well as comparatives and superlatives.